Resistansi dan Model Resistansi dalam Novel Perempuan Berkalung Sorban Karya Abidah El Khalieqy - Wildan Wildan (Kantor Bahasa Provinsi Maluku Utara, 2014)
The research on “Perempuan Berkalung Sorban” aimed at revealing aesthetic reconstructive model of gender discrimination in an Islamic boarding school environment and the model of aspired gender equality.This research used feminist literary criticism as a medium to express gender equality in the novel “Perempuan Berkalung Sorban”. Feminist literary criticism is regarded as a new life in a critique based on feelings,thoughts, and responses of the women based on the role vision and position in the literary world. Through the theory of feminist literary criticism, it could be concluded that the resistance and the model of gender equality in the novel ‘Perempuan Berkalung Sorban’ is a structured and massive gender discrimination which was built up from internal and external elements of literary works, such as the use of age, situation of the house, school and marriage. Meanwhile, Islam has been used as a shelter for the establishment of patriarchal culture in the different spheres of life. The model of gender equality was finally shown through Nisa’s second marriage with Khodori Lek. Nisa’s marriage was a marriage which became an ideal oraspired model of gender equality and a form of resistance to the first marriage with Syamsuddin.